Radiation dose assessment of soil from Ijero Ekiti, Nigeria. Issue 1 (1st January 2019) - Usikalu, M. R.; Maleka, P. P.; Ndlovu, N. B.; Zongo, S.; Achuka, J. A.; Abodunrin, T. J.
Abstract: The activity concentration of 238 U, 232 Th and 40 K in the soils of mining and living areas of Ijero Ekiti were determined using hyper pure germanium gamma ray spectrometer. The mean concentrations of 238 U, 232 Th and 40 K were found to be 128.05 Bqkg −1, 24.8 Bqkg −1 and 455.05 Bqkg −1, respectively, for mining areas, while it was found to be 42.02 Bqkg −1, 43.27 Bqkg −1 and 635.41 Bqkg −1, respectively, for the living areas. The mean absorbed dose rate, annual effective dose equivalent, gamma index and the excess lifetime cancer risk evaluated for the locations were 89.70 nGyh −1, 0.11 mSvy −1 and 1.4 for mining areas; while it was 72.22 nGyh −1, 0.089 mSvy −1 and 1.14 for living areas, respectively. The absorbed dose rate, annual effective dose equivalent and gamma index estimated for the mining site were higher than the living areas. The mean excess lifetime cancer risk estimated for the mining areas was consecutively higher than the recommended limit of 0.29 × 10 −3 for background radiation. It is therefore necessary for government to barn illegal mining activities going on in the town so as to reduce natural radiation burden from their operations in the town.